Conservação, germinação e efeitos alelopáticos de Lafoensia glyptocarpa Koehne - Moraes, Luiza Paiva Silva de (Universidade Federal de São Carlos, 2010)
The methodology of the accelerated aging test controlled deterioration to achieve the physiological quality of Lafoensia glyptocarpa Koehne seeds, separated into light and dark seeds, and to correlate if these seeds have their color due to different stages of maturation or whether the color is original phenotypic. The initial quality of the seeds was obtained through the tests of moisture content, conductivity and seedling emergence in greenhouse. The accelerated aging test was conducted at 40ºC during 24, 48, and 72 hours, using the traditional, NaCl saturated solution and controlled deterioration. The research was conducted in a completely randomized design. The saturated salt accelerated aging test and controlled deterioration was efficient for vigor evaluation of Lafoensia glyptocarpa Koehne seeds, and the period of 48hours at 40ºC was considered as the most adequate procedure to evaluate seed vigor levels, leading to the belief that colored seeds come from different stages of maturation.
Accelerated aging and controlled deterioration of Lafoensia glyptocarpa koehne seeds
Keywords: Fisiologia vegetal; Armazenamento; Sementes - envelhecimento; Alelopatia; Sinergismo; Deterioração controlada; Envelhecimento acelerado; Envelhecimento acelerado salino; Deterioração controlada; Condutividade; Lafoensia glyptocarpa; Accelerated aging; Salt accelerated aging; Controlled deterioration; Electrical conductivity; Lafoensia glyptocarpa; CIENCIAS BIOLOGICAS::ECOLOGIA